Different clinical courses of children exposed to a single incident of psychological trauma: a 30‐month prospective follow‐up study. (30th April 2014) - Hong, Soon‐Beom; Youssef, George J.; Song, Sook‐Hyung; Choi, Nam‐Hee; Ryu, Jeong; McDermott, Brett; Cobham, Vanessa; Park, Subin; Kim, Jae‐Won; Shin, Min‐Sup; Yoo, Hee‐Jeong; Cho, Soo‐Churl; et al.
<x xml:space="preserve">Abstract</x> Background We investigated the distinct longitudinal trajectories of posttraumatic stress symptoms in a sample of 167 children, who witnessed death of two mothers of their schoolmates. Methods The cohort was followed‐up at 2 days (T1), 2 months (T2), 6 months (T3), and 30 months (T4) after the traumatic event. The children's posttraumatic stress symptoms (T1–T4), depression (T1, T3 and T4), state anxiety (T1, T3 and T4), and quality of life (T4) were assessed, along with parental stress related to child rearing (T4). Different trajectory patterns of the children's posttraumatic stress symptoms were identified using growth mixture modeling (GMM). Results Four different patterns of symptom change were identified, which were consistent with the prototypical model, and were named Recovery (19.9%), Resilience (72.7%), Chronic Dysfunction (1.8%), and Delayed Reactions (5.6%). Significant differences were found in depression and anxiety scores, children's quality of life, and parental rearing stress according to the distinct longitudinal trajectories of posttraumatic stress symptoms. Conclusions The present study suggests that individual differences should be taken into account in the clinical course and outcome of children exposed to psychological trauma. The two most common trajectories were the Resilience and the Recovery types, together suggesting that over 90% of children were evidenced with a favorable 30‐month outcome. The latent classes were associated with significant mean differences in depression and anxiety scores, supporting the clinical validity of the distinct trajectories.